2006
DOI: 10.1111/j.1469-0691.2006.01499.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of environmental measures to decrease the risk of hospital-acquired aspergillosis in patients hospitalised in haematology wards

Abstract: This study evaluated a multidisciplinary strategy to decrease the rate of invasive pulmonary aspergillosis (IPA) among adult patients hospitalised in two haematology wards in a single 560-bed building at the University Hospital of Saint-Etienne. Upgrading of the air filtration system and construction of an air-lock chamber at the entrance to the unit were completed during 1994. In 1995, specific hygienic measures were introduced during hospital building work, including the use of plastic barriers, watering dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…In fungal infections caused by yeasts and other moulds, molecular studies have found a connection between the isolates collected from patients and from environmental samples (Cortez et al, 2008;Lupetti et al, 2002;Vos et al, 2006). Some studies have reported a decrease in the incidence of fungal infections in clinical units following a decrease in levels of airborne fungi (Alberti et al, 2001;Araujo et al, 2008b;Berthelot et al, 2006), but this improvement was not consistently found in all hospitals. One of the first studies reporting the absence of A. fumigatus infections in clinical environments with less than 0.1 CFU x m -3 was performed by Sherertz et al (1987).…”
Section: Air Quality and Fungal Infections 41 Hospital Indoor Air Qumentioning
confidence: 99%
“…In fungal infections caused by yeasts and other moulds, molecular studies have found a connection between the isolates collected from patients and from environmental samples (Cortez et al, 2008;Lupetti et al, 2002;Vos et al, 2006). Some studies have reported a decrease in the incidence of fungal infections in clinical units following a decrease in levels of airborne fungi (Alberti et al, 2001;Araujo et al, 2008b;Berthelot et al, 2006), but this improvement was not consistently found in all hospitals. One of the first studies reporting the absence of A. fumigatus infections in clinical environments with less than 0.1 CFU x m -3 was performed by Sherertz et al (1987).…”
Section: Air Quality and Fungal Infections 41 Hospital Indoor Air Qumentioning
confidence: 99%
“…Only building work considered to increase the risk of Aspergillus dissemination, with regards to the type and location, were taken into account according to the Assistance Publique-Hôpitaux de Paris scale. 20,21 The risk levels of hospital building work were expressed as a score taking into account the type and location of the work: score 1 for work taking place outdoors and at a distance; score 2 for minor renovation work taking place indoors on another floor; score 3 for work taking place outdoors in the proximity or with a prevailing wind; score 4 for minor renovation work indoors on the same floor or major renovation work on another floor; and score 5 for major renovation work on the same floor. The building work considered in this study had a score of 3 or more.…”
Section: Building Construction or Renovation Work And Environmental Mmentioning
confidence: 99%
“…It has also been reported that the incidence of IA is reduced to one-sixth when patients are managed with HEPA filtration after hematopoietic stem-cell transplantation (8,9). On the other hand, GM positivity was not increased in cases of acute leukemia, despite the severe myelosuppression associated with this condition.…”
Section: Discussionmentioning
confidence: 90%